Nonlinear control for a DC–DC converter with dual active bridges in a DC microgrid (2022)
This work presents a new control strategy for a DC–DC converter with dual active bridges used to interconnect two feeders in a DC microgrid. The proposed control strategy allows regulating the output voltage of the converter while maintaining the mean primary and secondary current value of the high-frequency transformer at zero, in order to avoid magnetic saturation. The controller is designed using the nonlinear control strategy based on feedback linearization, which is based on the converter generalized space-state averaged model. The performance of the proposed controller is validated via simulation and experimental results.